Secondary Metabolites and Antioxidant Activity of Methanol Extract and Fractions from the Root of Gitaan (Willughbeia coreacea Wall) - Rudiyansyah; Edwindar, Felgi; Ardiningsih, Puji (Al-Kimia, 2023)
Gitaan (Willughbeia coreaceae) is one of Indonesian endemic plants and belongs to Apocynaceae family that is potential for antioxidant source. This family contains triterpenoids, phenolics, alkaloids, and cardenolides, unfortunately information about secondary metabolites together with its biological activities from W. coreaceae is scarce. This study was conducted to determine secondary metabolites and antioxidant activity from the methanol extract and fractions of gitaan root. The root powder was macerated, its secondary metabolites were analyzed by phytochemical test and the antioxidant activity was evaluated by the qualitative and quantitative DPPH (1,1-diphenyl-2-picrylhydrazil) methods with the ascorbic acid was used as a positive control. Results showed the methanol extract and methanol fraction have alkaloids, polyphenols, and terpenoids, and ethyl acetate and n-hexane fractions contained alkaloids and polyphenols. By DPPH qualitative, all samples except for n-hexane fraction showed antioxidant properties which were indicated by yellow stains on the thin layer chromatography (TLC) plate after sprayed with 50 ppm of DPPH. By quantitative, methanol extract and fractions of methanol, ethyl acetate, n-hexane, and the ascorbic acid showed antioxidant activity with IC50 values of 44.1181 ppm, 45.4060 ppm, 57.2484 ppm, 983.9576 ppm, and 0.0445 ppm, respectively. Subsequently, methanol extract has better antioxidant activity then other fractions.